How a change to a more controlled start pace affects biathletes with a fast-start pacing pattern - Granrud, E. D. (Norwegian University of Science and Technology, 2022)
Purpose: In sprint biathlon with 3 equal laps, the most used pacing strategy is parabolic with the first and last lap being the fastest. However, as the best biathletes tend to have a more even pattern than the rest of the competitors, our aim was to investigate whether competitive junior biathletes with a fast-start pacing pattern increase time-trial performance by use of a more even pacing strategy.